2019
DOI: 10.1248/cpb.c19-00250
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Endomorphin-1 Derivative Functions as Self-assembling Nanomedicine for Effective Brain Delivery

Abstract: Endomorphin-1 (Tyr-Pro-Trp-Phe-NH 2 , EM-1), an endogenous μ-opioid receptor ligand with strong antinociceptive activity, is not in clinical use because of its limited metabolic stability and membrane permeability. In this study, we develop a short-peptide self-delivery system for brain targets with the capability to deliver EM-1 without vehicle. Two amphiphilic EM-1 derivatives, C 18-SS-EM1 and C 18-CONH-EM1, were synthesized by attaching a stearyl moiety to EM-1 via a disulfide and amide bond, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…(B) In vitro cytotoxicity of CPT, OEG-DiCPT, DOX⋅HCl, and OEG-DiCPT/DOX⋅HCl to MCF-7 breast cancer cells determined by MTT assay. 73 Copyright 2010, American Chemical Society stearic acid, 78 lauric acid, 79 phospholipid, [39][40][41][42][43] and so forth have been reported for self-assembled drug delivery. For example, Shen et al 73 reported the concept of directly using ethylene oxide oligomer to construct nanocarriers in order to minimize use of inert materials, substantially increase the drug loading content, and suppress premature burst release.…”
Section: Drug Derivativesmentioning
confidence: 99%
“…(B) In vitro cytotoxicity of CPT, OEG-DiCPT, DOX⋅HCl, and OEG-DiCPT/DOX⋅HCl to MCF-7 breast cancer cells determined by MTT assay. 73 Copyright 2010, American Chemical Society stearic acid, 78 lauric acid, 79 phospholipid, [39][40][41][42][43] and so forth have been reported for self-assembled drug delivery. For example, Shen et al 73 reported the concept of directly using ethylene oxide oligomer to construct nanocarriers in order to minimize use of inert materials, substantially increase the drug loading content, and suppress premature burst release.…”
Section: Drug Derivativesmentioning
confidence: 99%
“…Alkyl chain modification of peptides has received much attention in recent years (Evans et al 2020 ; Liu et al 2019 ; Yang et al 2023 ), since alkyl chain introduction renders peptides hydrophobic, which can induce peptide self-assembly and lead to the improvement of peptide drug stability (Gao et al 2023 ; Ding et al 2023 ; Yang et al 2023 ). Our previous study showed that self-assembled micelles formed by N-terminal myristoylated MVIIA at high concentrations can prolong the duration of analgesic effect, improve serum stability, and significantly reduce or even eliminate side effects (Ding et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%